Proton Conductivities of Lamellae-Forming Bioinspired Block Copolymer Thin Films Containing Silver Nanoparticles - Yabu, Hiroshi (Langmuir : the ACS journal of surfaces and colloids, 2016)
Size-controlled metal nanoparticles (NPs) were spontaneously formed when the amphiphilic diblock copolymers consisting of poly(vinyl catechol) and polystyrene (PVCa-b-PSt) were used as reductants and templates for NPs. In the present study, the proton conductivity of well-aligned lamellae structured PVCa-b-PSt films with Ag NPs was evaluated. We found that the proton conductivity of PVCa-b-PSt film was increased 10-fold by the addition of Ag NPs into the proton conduction channels filled with catechol moieties. In addition, the effect of humidity and the origin of proton conductivity enhancement was investigated